DVD copy protection take 2. - Perry, T.S (IEEE spectrum)
This paper describes the advanced access content systems (AACS), the copy protection scheme designed to keep future generations safe from pirated DVDs. The ACCS group was founded by IBM, Intel, Microsoft, Panasonic, Sony, Toshiba, Disney, and Warner Bros. Studios. The AACS specification allow customers to move the data on an optical disc to various devices they own, including video servers and portable video players, either directly or via a home network. In all the scenarios developed by the AACS alliance, that data would exist on the disc in encrypted form. It would stay encrypted when transferred to other devices and would be decrypted by those devices. ACCS used a so-called strong key, the 128-bit Advanced Encryption Standards that has the ability to keep on protecting data even after it has been cracked.